1982
DOI: 10.1159/000241600
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Corticosteroids on Glycogen Content and Steroid 11-Reductase Activity in Lung and Liver of the Fetal and Newborn Rat

Abstract: Lung and liver glycogen and corticosteroid 11-reductase activity were studied in fetal and neonatal rats. Glycogen content peaked in the lung on day 20 of gestation, while hepatic glycogen content was generally lower and peaked later. Both pre- and postnatally, betamethasone administration resulted in lowered pulmonary and elevated hepatic glycogen. In both lung and liver, corticosteroid 11-reductase activity showed an inverse developmental pattern to glycogen content. Betamethasone elevated pulmonary corticos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
2
6
1
Order By: Relevance
“…The rate of choline incorporation into phosphatidylcholine more than tripled between 19-20 days gestation and 1 day after birth. These profiles are similar to those previously reported for glycogen content (28,(30)(31)(32) and phosphatidylcholine synthesis (28,(33)(34)(35)(36) in the rat. Similar developmental profiles have been reported in other species (1,14).…”
Section: Resultssupporting
confidence: 90%
“…The rate of choline incorporation into phosphatidylcholine more than tripled between 19-20 days gestation and 1 day after birth. These profiles are similar to those previously reported for glycogen content (28,(30)(31)(32) and phosphatidylcholine synthesis (28,(33)(34)(35)(36) in the rat. Similar developmental profiles have been reported in other species (1,14).…”
Section: Resultssupporting
confidence: 90%
“…Although glucocorticoids have been shown to increase llß-HSD enzyme activity in the fetal rat lung (Smith et al 1982), adult mouse thymus (Dougherty et al 1960) and cultured human skin fibroblasts (Hammami & Siiteri 1991), under the conditions of the present study we found no effects of short-term glucocorticoid treatment on fetal pituitary llß-HSDl mRNA. However, we cannot rule out the possibility that long-term glucocorti¬ coid treatment may be effective in this regard.…”
Section: Resultscontrasting
confidence: 82%
“…Recent studies by Smith and Sabry [28] on 20-day-old fetal lung cul tures indicate that cortisol induced the syn thesis of a mesenchymal fibroblast-pneumonocyte factor which interacts with recep tors on the cell surface of alveolar type-11 cells to elevate intracellular level of cyclic AMP. An elevation in cyclic AMP presum ably initiates a cascade of enzyme reactions resulting in enhanced glycogen breakdown to glycolytic intermediates such as the aglyceraldehyde phosphate, dihydroxyacetone phosphate or acetate, all of which are utilized for the synthesis of phospholipids [22,29], Although we could not demon strate in vivo any effect of dexamethasone administration to pregnant rats on the fetal lung factor(s) potentiating adenylate cyclase activity to produce more cyclic AMP, the results of the present study and those of Smith and Sabry [28] support the earlier observations of Barrett et al [2,3] that cor ticosteroids enhance fetal lung maturation via cyclic AMP. The mechanism(s) by which corticosteroids elevate cyclic AMP in fetal lungs is not clearly understood.…”
Section: Discussionmentioning
confidence: 99%